Bioaccesibilidad de DHA EPA y ala en hamburguesas de boquichico (Prochilodus nigricans) bajas en sodio enriquecidas con ácidos grasos poliinsaturados - Bazán Ferrando, Alberto José (2024)
The present study was developed at the UNAP Natural Resources Research Center in 2022 and focuses on evaluating the bioaccessibility of docosahexaenoic (DHA), eicosapentaenoic (EPA) and α-linolenic (ALA) acids in hamburgers of boquichico (Prochilodus nigricans) made with microencapsulated oil from fish (Brevoortia tyrannus) and sacha inchi (Plukenetia volubilis L.). The structure of the microparticles was modified with the enzyme transglutaminase and added to the hamburgers. DHA, EPA and ALA fatty acids released during in vitro gastrointestinal simulation showed a similar behavior, the highest amount released was observed in the intestinal stage followed by the gastric and buccal stage. The bioaccessible percentages of DHA, EPA and ALA in the burger enriched with fish oil (HAP) were 44.04 ± 5.58 %, 50.54 ± 0.94 % and 30.56 ± 2.57 %, respectively, and in the burger enriched with sacha inchi oil (HASI), were 31.01 ± 10.16 %, 41.64 ± 5.79 % and 35.40 ± 7.24 %, respectively. The HAP burger reaches the amount of EPA + DHA recommended for consumption per day. Finally, the importance of quantifying the amount of EPA and DHA in the fortified food and the bioaccessible amount of these compounds in the food matrix is shown.